Molecular conformation of polymers in a H-shaped micro-channel - Liew, Xu Tat (2016)
Owing to differences in properties, Newtonian and non-Newtonian liquids behave differently in micro-channels. Although the flow of Newtonian liquid in a micro-channel is laminar, the addition of a small amount of polymer can induce elastic forces that cause flow instability. Hitherto, investigations have reported that the flow instability is due to the elastic characteristic of the polymer, although observation of polymer molecules through physical visualisation is limited. Thus, this report sets out to look into the molecular conformation of polymer molecules by infusing partially hydrolysed polyacrylamide into a H-shaped micro-channel. Results from the experiment showed that the polymer molecules displayed stretching behaviour at various positions of the micro-channel which can indeed be traced towards the elastic characteristic of the polymer.